Actual Vectors of Research in the Doctrine of the Judiciary - SKRYPNIUK, Valentyna M.; BULKAT, Maryna S.; DROBOTOV, Serhii A. (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019DO - 10.14505/jarle.v10.7(45).22, 2019)
The ways in which international entities and the judiciary function are of global importance. Each state has different strategies for resolving and developing the activities of national judicial systems, ways of executing decisions, investigating subjects, and ways of exercising judicial power. This article explores the ways and effectiveness of implementing the mediation institute and mediation judges using the Ukrainian space. The authors examined the models of mediation, the levels of responsibility of the subject-carrier of mediation powers, the functional potential of mediation. The article also gives examples of integration of national judicial systems into the international system. As a result of the study, the authors outline ways to introduce mediation and select appropriate models and outline key approaches of correlation of national judicial systems with intergovernmental bodies and coordination of national judicial systems with judicial authorities. This article may form the basis for further exploration of the doctrines of the judiciary.